Physico-chemical parameters and sensory attributes of different chicken meat of consumer’s choice from poultry market - Bostami, ABM Rubayet; Khan, MRI; Selim, ASM; Hossain, MD; M Khairunnesa (Meat Research, 2022)
Generally, consumers prefer the indigenous chicken meat compare to commercial chicken like sonali or broiler chicken because of their concept of having more nutritious and palatability and ready to pay more. Whether the concept is true or not, and on which aspects, indigenous chicken meat is superior compare to that of commercially reared chicken, validation is required. Therefore, an experiment was conducted to compare the carcass characteristics, meat proximate composition, physico-chemical parameters and sensory attributes of indigenous/deshi, sonali and broiler chicken that are available in the poultry market of Bangladesh. Three types of finisher chicken: indigenous/deshi, sonali and broiler chicken were bought from local market of Bangladesh. Birds were slaughtered following halal method; carcass traits and meat quality parameters were analyzed after collection and processing of meat samples. Result indicated that, there is a variation in the carcass characteristics, proximate composition, physico-chemical attributes and sensory evaluation. Broiler chicken live weight, slaughter weight and abdominal fat was higher as compared to sonali and indigenous/deshi chicken (P<0.05). The dry matter, crude protein and ether extract was higher in deshi chicken followed by sonali and broiler chicken (P<0.05). Drip loss and cooking loss was higher in broiler chicken followed by sonali and deshi chicken, while pH24 was lower in deshi chicken followed by sonali and broiler chicken (P<0.05). Broiler chicken meat was more tender in relation to sonali and deshi chicken (P<0.05), where flavor of deshi chicken meat was higher as compared to the broiler chicken (P<0.05). Result suggested that, based on level of status of people, consumers can choose indigenous or deshi chicken due to better proximate composition and meat flavour; however, sonali and broiler chicken are also acceptable by the consumers with higher carcass weight and meat tenderness with short interval to become marketable weight and cheap price which can be afford by all class of people to meet their protein demand, eventually can secure national human health.